Supplementation in Infertility: A Narrative Literature Review - Woźniak, Kinga; Bieniek, Maciej; Dachowska, Sandra; Haraj, Jan; Sobkowiak, Marcin; Namysł, Maria; Matczak, Simon; Fałczyńska, Aleksandra; Wawrzyniak, Maria (Journal of Education, Health and Sport, 2026)
Infertility is a significant global health issue. It can have profound medical, psychological, and social consequences. As medical understanding of reproductive health advances, numerous factors contributing to reduced fertility have been identified. In recent years, nutritional supplementation has gained increasing attention as a potential adjunct to standard infertility treatments. Research now investigates its roles in various biological and reproductive processes. To review current knowledge on the role, safety, and mechanisms of nutritional supplements in infertility treatment. We conducted a narrative review of scientific literature from 2012 to 2025. The search included PubMed, Cochrane Library, Web of Science, and Google Scholar. We included randomized controlled trials, meta-analyses, systematic reviews, and guidelines from scientific societies. Studies of low methodological quality were excluded. The strongest evidence supports folic acid supplementation, which acts as a methyl donor to improve oocyte quality and prevent neural tube defects. Myo-inositol demonstrated 85% effectiveness in restoring ovulation in women with polycystic ovary syndrome. Coenzyme Q10 improves oocyte quality, especially in women over 35 years old. Antioxidants and minerals support sperm health by reducing oxidative stress and enhancing seminal parameters. Omega-3 polyunsaturated fatty acids modify cell membrane fluidity to enhance sperm quality, particularly when the omega-6/omega-3 polyunsaturated fatty acids ratio is optimized. Probiotics may support treatment by promoting a healthy gut microbiota and lowering systemic oxidative stress. Nutritional supplementation is a promising supportive approach in infertility treatment. What is more, personalized supplementation based on metabolic and genetic profiles is a future direction. Supplements are generally safe at recommended doses; however, precautions against overdose and self-medication are essential.